Resistensi Ideologi Sosialisme terhadap Ideologi Kapitalisme (Membumikan Kembali Pemikiran Tan Malaka dalam Sejarah Indonesia) - Alamudi, Ichwan Ahnaz (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2023)
Tan Malaka's economic politics are characterized by two separate terms: politics in the style of communism and economics in the style of socialism. These concepts represent resistance against the hegemony of capitalism in Indonesia, which, from a historical perspective, began to evolve into global capitalism following the Industrial Revolution. Tan Malaka sought 100% independence for the republic through a path of social revolution, advocating resistance and mass movements. Mass Action towards Social Revolution was seen as the final means to achieve complete independence, specifically in opposing the hegemony of imperialism, colonialism, and capitalism. Socialism was envisioned as a means to liberate the nation from foreign influence by eliminating social classes, thereby eradicating oppression, slavery, and capitalist exploitation.